Ethical reflection in cognitive behavioral therapy and supervision: Theory and practice - Prasko, Jan; Burkauskas, Julius; Bělohradová, Kamila; Kantor, Krystof; Vanek, Jakub; Abeltina, Marija; Juskiene, Alicja; Slepecky, Milos; Ociskova, Marie (Neuro-endocrinology letters, 2023)
Ethical reflection is a process that comes from the deeper attitudes and values of the therapist and supervisor. The capability to recognize one's perspectives and ethical dimensions and how they affect own practice is one of the crucial tasks of a responsible therapist. Attitudes and values of an individual or a group may significantly influence the therapeutic process and a choice of strategies and behaviour towards the patient, often working at an unconscious, unreflected levels. Ethics is closely connected with psychotherapeutic treatment. Basic principles, such as expediency, honesty, integrity, justice, and respect, apply to all people equally, including psychologists, psychiatrists, psychotherapists, and supervisors. The goal of supervision is to cultivate the therapeutic process in the client's best interest. The supervisor-supervisee relationship is then grounded on principles similar to those in the therapeutic relationship.
Keywords: kognitivně behaviorální terapie; Psychotherapy; lidé; Brassicaceae; psychoterapie; Cognitive Behavioral Therapy; Humans